The Role of Attachment Styles in Vulnerability to Love-bombing and its Psychological Consequences ([s.l.] : [s.n.], 2024)
Love-bombing characterized by overwhelming praise and attention, can lead to significant psychological harm. This study investigated how attachment styles influence susceptibility to love-bombing, contributing factors and its effects using surveys and interviews. Using Spearman Rho, results showed that individuals with disorganized attachment styles (r=0.177 at p-value of 0.0001) are particularly vulnerable due to their conflicting needs for connection and fear of intimacy stemming from inconsistent or harmful early relationships. However, participants with various attachment styles also reported susceptibility under specific circumstances. Twelve (12) participants that was qualifies for the second phase (interview) were selected through an inclusion criteria. Themes were generated using thematic analysis, psychological consequences included confusion, trust issues, dependency, emotional insecurity, and obsession. To counteract these effects, participants identified coping strategies such as seeking social support, setting boundaries, and enhancing self-awareness. The findings emphasize the importance of recognizing love-bombing behaviors early to protect against manipulation and psychological harm.
Rosselle M. Obra [et al.]
Keywords: Love-bombing; Attachment styles; Love-bombing -- vulnerability